Det mobila drickandets logistik - Gay Hawkins (Kulturella Perspektiv, 2013)
This essay investigates the relatively new practice of carrying bottled water as a personal health accessory. The focus in on how this practice emerged and how it can be challenged. It would be easy to assume that pedestrians began carrying water because of the decline of clean, public water fountains in urban space. There is little evidence to support this. Instead, it seems that carrying bottled water is much more linked to new marketing discourses on hydration and health. In the transformation of thirst into ‘daily hydration needs’ consumers were advised to drink water constantly, this could only be achieved by having a personal supply on hand at all times. The other key factor was the rise of the PET bottle. This lightweight unbreakable container was the perfect device to format a new drinking conduct. Carrying bottled water is a consumption practice that has developed in relation to new discourses about health and water, and new packaging materials. In the second half of the essay I investigate how this carrying practice has been challenged by the reintroduction of water fountains. In investing in free supplies of water in urban space, we see how a ‘public thing’ such as a water fountain challenges a carrying practice. This public thing creates a water commons of all those who are implicitly linked by the act of sharing, rather than carrying, water.